A Comparative Evaluation of AI Agent Orchestration Frameworks for Regulated Environments - Zukeram, Renzo; Mergulhão, Vinícius; Medeiros, Yuri de; Melo, Marcantoni; Santos Júnior, Ramiro; Loss, Stefano; Cacho, Nélio; Lopes, Frederico (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
Organizations operating under compliance mandates increasingly rely on AI agents to automate workflows involving unstructured documents and dynamic decision-making. In such settings, agentic systems must reconcile autonomy with strict requirements for auditability, controlled variability, and integration with legacy infrastructures. We propose an Exemplar as a reusable evaluation artifact for analyzing agentic orchestration frameworks under Compliance Management and Documentary Uncertainty. The Exemplar captures the interaction between probabilistic extraction and deterministic constraint enforcement in workflows characterized by unstructured inputs, rigid schemas, and asynchronous processes. We empirically evaluate four frameworks (CrewAI, Embabel, LangChain, and n8n) across three dimensions: type safety, reasoning auditability, and legacy interoperability. The evaluation is grounded in a real-world instantiation within a state penitentiary agency, involving automated processing of employment contracts with incomplete data and asynchronous stakeholder interactions. Results show clear trade-offs between flexibility and control, highlighting the importance of hybrid approaches that combine agentic reasoning with deterministic validation. The exemplar generalizes to regulated domains such as public procurement, finance, and healthcare.